Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.

Transfer hydrogenation of biomass-derived levulinic acid to gamma-valerolactone over supported Ni catalysts - Hengne, Amol M.; Kadu, Brijesh S.; Biradar, Narayan S.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (RSC Advances, 2016)
A sustainable process of catalytic transfer hydrogenation (CTH) of levulinic acid (LA) to gamma-valerolactone (GVL) was investigated over Ni on various supports (Al2O3, ZnO, MMT and SiO2) in the presence of isopropanol (IPA) as the H-donor. Among these, the montmorillonite (MMT) supported Ni catalyst showed almost complete LA conversion (>99%) and selectivity (>99%) to GVL within 1 h. XRD and XPS results showed that the concentration of the metallic species significantly enhanced (two to four times) in the recovered sample as compared to the freshly prepared Ni/MMT. This was due to the in situ reduction of Ni2+ species present on the catalyst surface, through liberated H-2 under the reaction conditions. The strong acid strength of MMT, evidenced by NH3-TPD and py-IR, facilitated the esterification of LA as well as cyclization to GVL. The conversion-selectivity pattern was found to decrease in the IPA-water mixture while, it remained unchanged in the IPA-acetone mixture. Our catalyst could be efficiently recycled up to five times with consistent CTH activity and selectivity to GVL. The plausible mechanism of LA to GVL conversion involves the formation of a levulinate ester with IPA that favours its simultaneous hydrogenation and cyclization in a spontaneous manner to give GVL and regenerating IPA for sustainability.